A patient self-report disability identifier within health service electronic medical records: evaluation of patient, carer and clinician acceptability - Joanne Rowe; Alexandra Devine; Nicole Merrick; Marie Huska; Kristen Morris; Kath Feely; Ahuva Segal; Louise Mogg; Jenni Medland; Rebecca Jamwal; Alison Smith; Maricar Gleich; et al. (BMC Health Services Research)
Abstract Background A third of the 5.5 million Australians with a disability require adjustments to access healthcare effectively. Ensuring clinicians have timely information about a patient’s disability and care needs can support more responsive care. Disability Identifiers—brief question sets—offer a practical way to capture this information. However, their use in healthcare remains limited. To address this, a group of clinicians, consumers and researchers from five tertiary and quaternary health services in Victoria, Australia, co-designed and implemented a patient self-report Disability Identifier within Electronic Medical Record systems. This paper presents an evaluation of the acceptability of this intervention among patients, carers, and clinicians. Methods The Disability Identifier questions were integrated into Electronic Medical Record systems across the five health services in March 2023, with the evaluation period spanning the first nine months of implementation (1st March–30th November 2023). Using a mixed methods convergent parallel design and guided by the Theoretical Framework of Acceptability, we conducted online surveys, interviews, and focus groups with patients, carers, and clinicians. Data analysis explored perspectives and experiences across eight constructs: general acceptability, affective attitude, burden, ethicality, intervention coherence, opportunity costs, self-efficacy, and perceived effectiveness. Results Survey results indicated strong acceptability of the Disability Identifier questions. Interviews with patients and carers reflected generally positive perceptions of the intervention, with many noting that it signalled a commitment by health services to improve care for people with disability. Clinicians emphasised that, with adequate training and resources, this intervention could raise awareness about disability and contribute towards disability-responsive care. Conclusions Integrating patient self-reported Disability Identifiers into EMR systems marks a critical step toward improving disability-responsive healthcare. Building trust in Disability Identifiers requires clear communication about their purpose, benefits, and role in improving care while also addressing disability awareness and discrimination in healthcare settings. While continuous evaluation of their use and impact on patient experiences and outcomes is recommended, this research lays the foundation for other jurisdictions to adopt a standardized approach to integrating Disability Identifiers into health data systems. Ultimately, effective use of patient self-report Disability Identifiers has the potential to promote more equitable health outcomes for people with disability.